2019
DOI: 10.1074/jbc.ra119.009685
|View full text |Cite
|
Sign up to set email alerts
|

Molecular underpinnings of integrin binding to collagen-mimetic peptides containing vascular Ehlers–Danlos syndrome–associated substitutions

Abstract: Collagens carry out critical extracellular matrix (ECM) functions by interacting with numerous cell receptors and ECM components. Single glycine substitutions in collagen III, which predominates in vascular walls, result in vascular Ehlers-Danlos syndrome (vEDS), leading to arterial, uterine, and intestinal rupture and an average life expectancy of <50 years. Collagen interactions with integrin ␣ 2 ␤ 1 are vital for platelet adhesion and activation; however, how these interactions are impacted by vEDS-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 96 publications
3
8
0
Order By: Relevance
“…However, the introduction of Gly→Arg within the IBS of bacterial collagen, VCL 2 (G→R)-Trypsin, increased sensitivity to trypsin digestion with detectable CL 2 cleavage products after only 2 minutes ( Fig 5B ). This is consistent with the highly disruptive nature of Gly→Arg substitutions within the triple helix [ 22 , 28 30 ]. After overnight digestion with trypsin, the VCL 2 (G→R)-Trypsin protein is entirely degraded, hampering purification and significantly reducing the final yield of CL 2 (G→R).…”
Section: Resultssupporting
confidence: 76%
“…However, the introduction of Gly→Arg within the IBS of bacterial collagen, VCL 2 (G→R)-Trypsin, increased sensitivity to trypsin digestion with detectable CL 2 cleavage products after only 2 minutes ( Fig 5B ). This is consistent with the highly disruptive nature of Gly→Arg substitutions within the triple helix [ 22 , 28 30 ]. After overnight digestion with trypsin, the VCL 2 (G→R)-Trypsin protein is entirely degraded, hampering purification and significantly reducing the final yield of CL 2 (G→R).…”
Section: Resultssupporting
confidence: 76%
“…To investigate the specific effect of metal ions on the binding of the structural domain of α 2 I, we performed ELISA experiments . α 2 I interaction with collagen depends on the coordination of divalent metal cations to Glu in the recognition structural domain. , Therefore, binding assays were performed in the presence of Mg 2+ and Ca 2+ and in the absence of both cations to control for nonspecific binding.…”
Section: Resultsmentioning
confidence: 99%
“…For example, CMPs were designed to include reported Gly → X (X = Ala, Arg, and Val) substitutions occurring within the high-affinity integrin α2β1 binding motif, GROGER, in vascular EDS patients. These mutated sites were flanked with (GPO) n sequences at both ends [138] . The study again demonstrated that the identity of the residue in a Gly → X substitution could have a range of impacts on triple helix stability, binding with the integrin α2-inserted (α2-I) domain, and the expected severity of a disease phenotype [138] .…”
Section: In Vitro Studies To Examine the Structure–function ...mentioning
confidence: 99%
“…These mutated sites were flanked with (GPO) n sequences at both ends [138] . The study again demonstrated that the identity of the residue in a Gly → X substitution could have a range of impacts on triple helix stability, binding with the integrin α2-inserted (α2-I) domain, and the expected severity of a disease phenotype [138] . Cell adhesion assays demonstrated that human mesenchymal stem cells (hMSCs) grown on the Gly → Ala peptide exhibited strong cell adhesion similar to wild-type peptides, while cells cultured on Gly → Val peptide adhered poorly, and those that were adherent displayed altered morphology with a “pancake-like” appearance [138] .…”
Section: In Vitro Studies To Examine the Structure–function ...mentioning
confidence: 99%